1998
DOI: 10.1016/s0735-1097(98)00006-0
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin Anticoagulation and Survival: A Cohort Analysis From the Studies of Left Ventricular Dysfunction 11This study was supported by Grant MO1-RR00054 from the General Clinical Research Center, funded by the Division of Research Resources, National Institutes of Health, Bethesda, Maryland. The Studies of Left Ventricular Dysfunction (SOLVD) were funded by the National Heart, Lung, and Blood Institute, National Institutes of Health, Bethesda, Maryland, with a contribution from Merck, Sharpe and Dohme Pha

Abstract: In patients with LV systolic dysfunction, warfarin use is associated with improved survival and reduced morbidity. This association is primarily due to a reduction in cardiac events and does not appear to be limited to any particular subgroup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Administration of subcutaneous heparin after thrombolysis for a STEMI [12], or alone in anterior STEMI [41], also did not demonstrate an effect on stroke. In a retrospective analysis [42], warfarin use in patients with heterogeneous causes of chronic left ventricular dysfunction demonstrated improved survival and risk of hospitalization for heart failure, but had no effect on stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of subcutaneous heparin after thrombolysis for a STEMI [12], or alone in anterior STEMI [41], also did not demonstrate an effect on stroke. In a retrospective analysis [42], warfarin use in patients with heterogeneous causes of chronic left ventricular dysfunction demonstrated improved survival and risk of hospitalization for heart failure, but had no effect on stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective analyses of HF studies have suggested a mortality reduction by anticoagulants in HF [32, 33]. Death and intracerebral hemorrhage were included in the primary WARCEF endpoint as they are major life-altering events that may be influenced by warfarin.…”
Section: Warcef Combined Endpoint Of Ischemic Stroke Intracerebral Hmentioning
confidence: 99%
“…Up to 28% of HF individuals in sinus rhythm are currently treated with warfarin. (11;12) Many individuals with HF on warfarin may not be benefiting from it or may be suffering needless hemorrhagic complications. The aims of this study were firstly to examine the annual stroke rate in participants of the REGARDS study with HF without AF and also in subgroups of participants with vascular risk factors to determine if a subgroup with a stroke rate high enough to warrant anticoagulation can be identified.…”
Section: Introductionmentioning
confidence: 99%